2016
DOI: 10.1021/acs.energyfuels.6b01148
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Fructose and 5-Hydroxymethylfurfural into 2,5-Diformylfuran over SBA-15 Supported Ruthenium Catalysts

Abstract: In this study, the mesporous SBA-15 was prepared and used to graft biimidazole groups, which were used to anchor Ru 3+ to give rise to a new ruthenium catalyst (SBA-15-Biimidazole-Ru). The structure of the SBA-15-Biimidazole-Ru catalyst was well characterized and used for the aerobic oxidation of 5-hydroxymethylfurfural (HMF) into 2,5-diformylfuran (DFF). Several important parameters were studied and found that the reaction solvent and oxygen pressure showed a crucial role in the activity of the as-prepared SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In Figure 1b, it can be seen that after calcination in the air, diffraction peaks of hydrotalcite is disappearing and instead new eighty diffraction peaks were observed. The presence of new paek at a 2θ value of 19,31,36,39,45,55,59 and 65 confirms the presence of oxide spinel phase (JCPDS 38-0814). Thus, after calcination XRD results show the conversion of hydrotalcite phase into mixed metal oxide phase.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…In Figure 1b, it can be seen that after calcination in the air, diffraction peaks of hydrotalcite is disappearing and instead new eighty diffraction peaks were observed. The presence of new paek at a 2θ value of 19,31,36,39,45,55,59 and 65 confirms the presence of oxide spinel phase (JCPDS 38-0814). Thus, after calcination XRD results show the conversion of hydrotalcite phase into mixed metal oxide phase.…”
Section: Resultsmentioning
confidence: 52%
“…Different types of solid acid catalyst such as acidic cation‐exchange resin, Amberlyst‐15, Fe 3 O 4 ‐RGO‐SO 3 H, CrCl 3 ⋅6H 2 O/NaBr/ NaVO 3 ⋅2H 2 O and Fe 3 O 4 ‐SBA‐ SO 3 H are used for the dehydration of fructose to HMF. These solid acids in collaboration with metals or metal oxide (V‐based compound, Ru/HT, ZnFe 1.65 Ru 0.35 O 4 , VOHPO 4 and SBA‐15‐ biimidazole‐Ru) catalyst are employed for the selective oxidation of HMF to DFF . The applicability of such combined catalytic system is limited by the decomposition of fructose in the presence of molecular oxygen or air there by leading to a significant decrease in DFF yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid depletion of non‐renewable resources and the rising concerns about global warming moved the research towards the synthesis of transportation fuels and value added chemicals from renewable resources . 5‐hydroxymethylfurfural (HMF) is a platform molecule derived from dehydration of monosaccharides using homogenous and/or heterogeneous acid catalysts such as CrCl 3 + HCl, formic acid + H 2 SO 4 , Fe 3 O 4 ‐SBA‐SO 3 H, Amberlyst‐15, Hydrotalcites, acidic cation‐exchange resin, etc . Conversion of HMF into value‐added products such as 2,5‐dimethylfuran (DMF), 2,5‐furan‐dicarboxylic acid (FDCA), Maleic anhydride (MA), 2,5‐ diformylfuran (DFF), and levulinic acid is highly explored research area by various institution .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported the DFF synthesis based on a one-pot approach. Starting from fructose, two catalysts were used sequentially, fructose dehydration using an Amberlyst 15 catalyst and the subsequent oxidation of HMF using an Ru-based catalyst, and the DFF yield was 72.4% [7]. The Amberlyst 15 catalyst was used together with hydrotalcite-supported Ruthenium catalysts for the synthesis of DFF [8].…”
Section: Introductionmentioning
confidence: 99%